2009
DOI: 10.1002/ibd.20926
|View full text |Cite
|
Sign up to set email alerts
|

Filaggrin loss-of-function variants are associated with atopic comorbidity in pediatric inflammatory bowel disease

Abstract: Filaggrin null-alleles have no effect on IBD susceptibility but contribute to coexistent eczema and food allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…Of particular note, the oral cavity has been shown to highly express the epithelial barrier protein filaggrin (a strong genetic determinant of atopic eczema), 4 with null alleles of its coding gene FLG contributing to coexistent eczema and food allergy in pediatric IBD patients. 5 The epithelium lining the remainder of the gut is composed of nonciliated, columnar epithelium. This rapidly self-renewing tissue is primarily involved in the absorption of water and nutrients, but also has a vital role in acting as a barrier to luminal pathogens.…”
Section: Epithelial Monolayer Epithelium Structurementioning
confidence: 99%
“…Of particular note, the oral cavity has been shown to highly express the epithelial barrier protein filaggrin (a strong genetic determinant of atopic eczema), 4 with null alleles of its coding gene FLG contributing to coexistent eczema and food allergy in pediatric IBD patients. 5 The epithelium lining the remainder of the gut is composed of nonciliated, columnar epithelium. This rapidly self-renewing tissue is primarily involved in the absorption of water and nutrients, but also has a vital role in acting as a barrier to luminal pathogens.…”
Section: Epithelial Monolayer Epithelium Structurementioning
confidence: 99%
“…There was no association found between disease and FLG mutations [ 13 ]. A second study of a cohort of 378 Scottish children with IBD found that 40 of the children (10.6 %) were found to be carriers of one or more FLG null alleles, compared to 103/944 (10.9 %) of controls [ 14 ]. Although no link has yet been established between FLG mutations and the development of IBD, it remains possible that fi laggrin, if expressed, may affect gut barrier functions and alter the risk of various GI disorders.…”
Section: Filaggrin and Infl Ammatory Bowel Diseasementioning
confidence: 90%
“…A study by Van Limbergen et al found a 4.5-fold increased risk of food allergy in carriers of FLG mutations (R501X and 2282del4) in a cohort of children with pediatric infl ammatory bowel disease (IBD) susceptibility and coexistent atopy (median age 11.3 years) [ 49 ]. The food allergy status was parent reported, and food sensitization status was unknown.…”
Section: What Is the Evidence That The Flg Might Be Involved In Food mentioning
confidence: 98%
“…The food allergy status was parent reported, and food sensitization status was unknown. Skin prick tests, food challenges, and specifi c IgE assays were not performed as food allergy was not part of the original study protocol [ 49 ].…”
Section: What Is the Evidence That The Flg Might Be Involved In Food mentioning
confidence: 99%